Outcome After Surgery Alone or With Restricted Use of Chemotherapy for Patients With Low-Risk Neuroblastoma: Results of Children's Oncology Group Study P9641 - Strother, Douglas R. (American Society of Clinical Oncology, 2012)
PURPOSE: The primary objective of Children's Oncology Group study P9641 was to demonstrate that surgery alone would achieve 3-year overall survival (OS) ≥ 95% for patients with asymptomatic International Neuroblastoma Staging System stages 2a and 2b neuroblastoma (NBL). Secondary objectives focused on other low-risk patients with NBL and on those who required chemotherapy according to protocol-defined criteria. PATIENTS AND METHODS: Patients underwent maximally safe resection of tumor. Chemotherapy was reserved for patients with, or at risk for, symptomatic disease, with less than 50% tumor resection at diagnosis, or with unresectable progressive disease after surgery alone. RESULTS: For all 915 eligible patients, 5-year event-free survival (EFS) and OS were 89% ± 1% and 97% ± 1%, respectively. For patients with asymptomatic stage 2a or 2b disease, 5-year EFS and OS were 87% ± 2% and 96% ± 1%, respectively. Among patients with stage 2b disease, EFS and OS were significantly lower for those with unfavorable histology or diploid tumors, and OS was significantly lower for those ≥ 18 months old. For patients with stage 1 and 4s NBL, 5-year OS rates were 99% ± 1% and 91% ± 1%, respectively. Patients who required chemotherapy at diagnosis achieved 5-year OS of 98% ± 1%. Of all patients observed after surgery, 11.1% experienced recurrence or progression of disease. CONCLUSION: Excellent survival rates can be achieved in asymptomatic low-risk patients with stages 2a and 2b NBL after surgery alone. Immediate use of chemotherapy may be restricted to a minority of patients with low-risk NBL. Patients with stage 2b disease who are older or have diploid or unfavorable histology tumors fare less well. Future studies will seek to refine risk classification.